Science and Technology Publications Associated with the University of Mysore: A Bibliometric Examination Using Web of Science Database - H., Satheesha; M, Chandrashekara (Cuestiones de Fisioterapia, 2025)
UoM (University of Mysore) reputations are significantly influenced by their publications. This bibliometric analysis, using VOSviewer, compiles Web of Science indexed papers from the University of Mysore (UoM), India. The number of publications from UoM has been steadily increasing.